Tertiary treatment of wastewater using multimedia filtration for solids removal - Ncube, Philani (Cranfield University, 2015)
The tightening of wastewater discharge standards for environmental protection and the increasing requirements for wastewater reuse have pushed for further tertiary treatment of wastewater to remove pollutants including suspended solids. This thesis explores the process science behind the removal of suspended solids from wastewater secondary effluent with the aim of improving the process for high quality effluent and efficient operation. Treatment plants receive diurnal flows and wastewater quality which challenges the production of a consistent compliant quality which meets reuse or discharge standards to receiving water bodies. A pilot-scale quadruple media filter was operated at the Cranfield Sewage Works to investigate the removal of suspended solids from secondary treated wastewater effluent under controlled and variable hydraulic loading rate, solids concentration and different wastewater characteristics. To measure the solids removal and operational performance of the filter, total suspended solids, turbidity, particle size analysis, zeta potential, headloss and temperature were measured under different operational conditions such as wastewater hydraulic loading rate, pH, solids concentration and filter depth. The media materials were examined to determine how they could be used to improve process performance and yield improved predictions in the application of filter models. A new method was developed for measuring the sphericity of media grains which improves the application of filter theory models to irregular shaped media grains. The method measured accurately the sphericity of glass spheres as 1.01 ± 0.02; the determined sphericity values correlated well with the measured headloss through filter media beds. The organic matter in the wastewater masked the media surface charge characteristics through coating on the media surface. Aggregation and deposition of wastewater solids was found to be most efficient near neutral pH. Adjustment of operational conditions were also explored. The solids removal efficiency of the filter varied inversely with an increase in hydraulic loading rate. However, multiple media layers reduced the negative impact of increased hydraulic loading rate and moderated headloss development. Particle retention was predominantly in the first 0.1 m depth of the filter, with further increases in filter depth producing marginal performance improvements whilst the headloss developed more quickly, reducing filter run times and wastewater throughput. While the specific deposit increased with rising influent concentration, the solids removal efficiency reduced. Thus, for an increase in the influent solids concentration of 10 mgL-1, the specific deposit increased by a factor of 1.2 while the removal efficiency decreased by an average factor of 0.9. Thus, the effluent deteriorates with increase in influent concentration while the filter holds more solids.
Keywords: Wastewater; depth filtration; granula media; porous media; multimedia; surface charge; zeta potential; particle size; shape; aggregation; deposition; hydraulic loading rate; flowrate; pressure drop; headloss; digital image processing (DIP); tertiary; secondary effluent; suspended solids; concentration